Peripheral Templation‐Modulated Interconversion between an A4L6 Tetrahedral Anion Cage and A2L3 Triple Helicate with Guest Capture/Release. (8th January 2018) - Bai, Xuemin; Jia, Chuandong; Zhao, Yanxia; Yang, Dong; Wang, Shi‐Cheng; Li, Anyang; Chan, Yi‐Tsu; Wang, Yao‐Yu; Yang, Xiao‐Juan; Wu, Biao
Abstract: An anion‐coordination‐based A4 L6 ("A" denotes anion and "L" is ligand) tetrahedral cage was constructed by a C2 ‐symmetric bis‐bis(urea) ligand and phosphate anion, which showed reversible interconversion with the A2 L3 triple helicate as a response to the template, concentration, or solvent. Notably, an unusual "peripheral" templation was found to be critical to stabilize the tetrahedral structure. This peripheral effect was utilized to assemble an "empty" A4 L6 cage that allows the multi‐stimuli‐controlled capture/release of biologically important species such as choline and acetylcholine.